Application of the ISSR method to estimate the genetic similarity of Dasypyrum villosum (L.) P. Candargy Greek populations to Triticum and Secale species - Grądzielewska, Agnieszka (Biodiversity: Research and Conservation, 2011)
In the study, the genetic similarity between Dasypyrum villosum L. (P.) Candargy and Triticum L. and Secale L. species was studied on the basis of ISSR markers. As a very polymorphic, effective and reproducible method, ISSR can be successfully employed to evaluate polymorphism between and inside different species. The polymorphic information content values (PIC) of ISSR method ranged from 0.57 to 0.87, with the mean value of 0.7. The genetic similarity of the forms analyzed ranged from 0.27 to 0.97, with the mean value of 0.47, indicating their high diversity. A higher similarity of Dasypyrum villosum to Triticum species, in comparison with Secale was found - the mean Dice genetic similarity index between genera was calculated at 0.40 for Dasypyrum and Triticum, and at 0.31 for Dasypyrum and Secale.